2023
DOI: 10.1021/acsaom.3c00337
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism and Photomagnetism in 1,4-bis(4,5-diphenyl-imidazolyl)benzene Chromophores: Water-Assisted π-Stacks for the Generation of Stable Free Radicals in the Solid State

Subhajit Saha,
Sudipta Khamrui,
Rajib Moi
et al.

Abstract: Photochromism and photomagnetism are two important properties for the generation of smart materials that are useful for optical switches and memory devices. Very few materials, mostly containing metal ions, are known to date to exhibit both properties at room temperature. Herein, we report a class of bis-imidazole-based organic molecules that show reversible photochromism and photomagnetism at room temperature due to the generation of free radicals in the solid state. 1,4-Bis(4,5-diphenyl-1H-imidazol-2-yl)benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Recently, we have shown that the as-synthesized 1,4-bis­(4,5-diphenyl-1 H -imidazol-2-yl)­benzene (BDPI) exists as a tetrahydrate for which the single crystals cannot be obtained . However, the crystal structure was determined by its powder diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that the as-synthesized 1,4-bis­(4,5-diphenyl-1 H -imidazol-2-yl)­benzene (BDPI) exists as a tetrahydrate for which the single crystals cannot be obtained . However, the crystal structure was determined by its powder diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…1–7 Conventional radical-doped organic materials may not only require complicated synthesis procedures, but also suffer from ready decomposition and photobleaching during practical application. 8–10 These shortcomings lead to increased costs and the risk of performance degradation. Therefore, it is necessary to design radical-doped materials with a stable structure and performance.…”
Section: Introductionmentioning
confidence: 99%